Effect of Training, Learning Environment and Learning Motivation of Student Competence in PPLP MAPINDO Tabanan - Ekadharma Susila, Bagus Putu; Lindawati, Ni Putu; Ariantini, Putu Oka (Akademi Komunitas MAPINDO, 2023)
This study aims to examine and analyze the effect of training, learning environment and learning motivation on the competence of students at PPLP Mapindo, Tabanan. The sample in this study were all students for the 2021/2022 Academic Year, a total of 50 students. Respondents' answers or responses will be processed by scoring/weighting using a Likert scale. Further analysis was carried out using multiple linear regression analysis techniques. Data collection methods using observation, interviews, questionnaires and documentation. The results of the research using the t statistical test (partial significant test) show that training, learning environment and learning motivation partially have a positive and significant effect on the competence of students in PPLP Mapindo - Tabanan. The training variable has a more dominant influence on the competence of students at PPLP Mapindo - Tabanan. The implication of this research is one of the considerations in efforts to maintain and improve the competence of students at PPLP Mapindo - Tabanan which can be done by maintaining the quality of training, learning motivation and improving the campus environment. Keywords: Training, Learning Environment, Learning Motivation, Competence